2012
DOI: 10.4067/s0716-078x2012000400005
|View full text |Cite
|
Sign up to set email alerts
|

Respuestas antioxidantes en dos ecotipos de Colobanthus quitensis (Caryophyllaceae) expuestos a alta radiación UV-B y baja temperatura

Abstract: Respuestas antioxidantes en dos ecotipos de Colobanthus quitensis (Caryophyllaceae) expuestos a alta radiación UV-B y baja temperatura Antioxidant responses in two Colobanthus quitensis (Caryophyllaceae) ecotypes exposed to high UV-B radiation and low temperature RESUMENColobanthus quitensis (Kunth) Bartl. (Caryophyllaceae) está distribuida desde México hasta la Antártida Marítima formando poblaciones adaptadas a distintas condiciones microambientales a lo largo de su distribución. La Antártica Marítima se ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…For instance, experiments performed in two Antarctic vascular plants have shown that while Deschampsia antarctica diverts c. 30% of its photosynthetic electron transport through the oxygen‐dependent sink, electron transport to oxygen in C. quitensis is negligible (Pérez‐Torres et al , ). The contribution of oxygen as an alternative electron sink relies on efficient detoxification of oxygen anion radicals to hydrogen peroxide and water by chloroplastic antioxidant enzymes, superoxide dismutase (SOD) and APX, respectively, consistent with the observation that D. antarctica has much higher SOD activity than C. quitensis (Navarrete‐Gallegos et al , ) and other cultivated Poaceae such as oat, barley or wheat (Pérez‐Torres et al , ). The importance of this pool of antioxidant enzymes has been confirmed using transgenic strategies.…”
Section: Photobiochemistrysupporting
confidence: 76%
“…For instance, experiments performed in two Antarctic vascular plants have shown that while Deschampsia antarctica diverts c. 30% of its photosynthetic electron transport through the oxygen‐dependent sink, electron transport to oxygen in C. quitensis is negligible (Pérez‐Torres et al , ). The contribution of oxygen as an alternative electron sink relies on efficient detoxification of oxygen anion radicals to hydrogen peroxide and water by chloroplastic antioxidant enzymes, superoxide dismutase (SOD) and APX, respectively, consistent with the observation that D. antarctica has much higher SOD activity than C. quitensis (Navarrete‐Gallegos et al , ) and other cultivated Poaceae such as oat, barley or wheat (Pérez‐Torres et al , ). The importance of this pool of antioxidant enzymes has been confirmed using transgenic strategies.…”
Section: Photobiochemistrysupporting
confidence: 76%
“…Previous reports of ChlF measurements on C. quitensis populations were exclusively focused in comparison with the Arctowski and La Parva populations under specific situations such as high UV-B radiation, low temperature, cold acclimation, and light intensity [ 14 , 24 , 25 , 26 ]. In general, in those studies, as with ours, Antarctic individuals showed higher photosynthetic performance than plants from La Parva.…”
Section: Resultsmentioning
confidence: 99%
“…(Caryophyllaceae) is a eudicotyledon, extremophile, stress-tolerant plant that inhabits low temperature environments from southern Mexico to maritime Antarctica. Given its wide geographical distribution and the isolation in which various populations of this species have developed, ecotypes adapted to particular environments have been generated [ 12 , 13 , 14 , 15 ]. The C. quitensis populations or geo-ecotypes show morphological and genetic variability, which is attributed to continuous selection processes in response to the environmental conditions prevailing in each habitat [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…quitensis became an interesting subject of morphophysiological investigations aiming to identify ecotypic variation (Gianoli et al 2004), to analyze its reproduction performance (Giełwanowska et al 2011;Sanhueza et al 2017) or identify the characteristic endophytic fungal communities (Santiago et al 2012(Santiago et al , 2017. Moreover, as the only representative of Magnoliopsida that grows in the extreme environmental conditions of the Antarctic, C. quitensis was extensively studied in terms of the morphological, physiological, and biochemical basis of adaptation to extremely cold climate, ample thermal oscillations, short vegetation season, high UV-B radiation, and salinity (Bravo et al 2007;Bascunan-Godoy et al 2012;Navarrete-Gallegos et al 2012;Cuba-Díaz et al 2017a). In contrast, the genetic diversity of this species is still poorly studied and deserves more attention.…”
Section: Genetic Diversity and Differentiation Of Colobanthus Quitensismentioning
confidence: 99%